Integrative taxonomy in the Liolaemus fitzingerii complex (Squamata: Liolaemini) based on morphological analyses and niche modeling - Minoli, Ignacio (2014)
It has long been considered sufficient a single method or only a descriptive diagnosis to propose a new species. Recently, many works have proposed new theoretical paradigms to consider multiple sources of evidence to support the hypothesis of new taxa within an integrative approach. Despite this, many new described species continue to be merely descriptive and without any reproducible statistical analysis to support these descriptions. We tested whether five species described as members of a species complex of the lizard genus Liolaemus from Patagonia, can be differentiated based on classical morphometric analyses and ecological niche modeling. Individuals were sampled from their type localities. Our results showed that the univariate tests and Principal Component Analyses (PCA) were more accurate to differentiate species compared to the Linear Discriminant Analyses (LDA). However, there were almost no morphometric differences between two of the analyzed species. Major differences were found in bioclimatic variables of four of the species through Maxent ENMs and PCA using the original worldclim variables. Our results partially support the hypothesis that species can be differentiated by classical morphometric analyses, and found a strong support for the hypothesis that these taxa can be differentiated through their bioclimatic niches. These two approaches based on repeatable statistical basis, can supplement qualitative descriptive diagnoses of new species of the genus Liolaemus.